Optimasi Infrastruktur Wi-Fi dan Manajemen Bandwidth di Sekolah Menengah Pertama Menggunakan Teknologi Mikrotik - Ramayanti, Desi; Saputra, Vega (Arcitech: Journal of Computer Science and Artificial Intelligence, 2025)
The increasing demand for reliable and high-performance Wi-Fi networks in educational institutions necessitates efficient infrastructure management. However, many schools still face issues such as poor signal strength and inefficient bandwidth allocation. This study aims to optimize Wi-Fi network infrastructure and bandwidth management using Mikrotik technology, addressing these limitations through strategic access point (AP) placement, Queue Tree-based bandwidth allocation, and real-time monitoring. A mixed-methods approach was used, combining quantitative performance measurements and qualitative user feedback. Results show significant improvements, with signal strength increasing from -83 dBm to -34 dBm, download speeds reaching 41.52 Mbps, and reduced latency in high-traffic areas. These findings suggest that proper infrastructure design and bandwidth management strategies can enhance network stability and efficiency in educational environments. This study contributes to the field by providing a practical model for Wi-Fi optimization in schools, potentially benefiting similar institutions globally.